Determination of nine prostaglandins in the arachidonic acid metabolic pathway with UHPLC-QQQ-MS/MS and application to in vitro and in vivo inflammation models - Yufeng Huang; Mengxian Wang; Mengxian Wang; Ziqi Yang; Ziqi Yang; Xiaotong Wang; Xinxin Wang; Fan He (Frontiers in Pharmacology)
BackgroundProstaglandins play a vital role as crucial metabolites and inflammatory indicators within the arachidonic acid (AA) metabolic pathway. Conventional assays typically focus on a single inflammatory indicator, while multi-index detection entails a large number of samples.MethodsIn this study, an ultra-high-performance liquid chromatography coupled with triple quadrupole mass spectrometry (UHPLC-QQQ-MS/MS) method was newly developed for simultaneous quantitative analysis of nine AA metabolites, including prostaglandin F2β (PGF2β), prostaglandin E2 (PGE2), prostaglandin E1 (PGE1), prostaglandin D1 (PGD1), prostaglandin D2 (PGD2), prostaglandin A2 (PGA2), prostaglandin J2 (PGJ2), prostaglandin B2 (PGB2), and prostaglandin A1 (PGA1), in the supernatant of LPS-induced RAW264.7 cells and the serum samples of adjuvant-induced arthritis (AIA) rats.ResultsThe newly established UHPLC-QQQ-MS/MS method successfully and rapidly quantified the contents of the nine prostaglandins simultaneously. The methodology was validated. The levels of PGE2, PGD1, PGD2, PGA2, and PGJ2 in the LPS-induced RAW264.7 cells group were higher than those in blank group. At the same time, the levels of these PGs decreased significantly (p < 0.01 vs. LPS-induced group) after the positive drug (dexamethasone) intervention. On the 14th day of AIA modeling, the paw volume of the AIA rats was significantly enlarged (p < 0.01 vs. blank group), and the serum samples from the AIA group showed significantly increased levels of PGE2, PGD2, and PGA2 (p < 0.01 vs. blank group), suggesting the emergence of arthritis. The levels of other prostaglandins were below the limit of quantification.ConclusionThe method established in this study for determining nine prostaglandins in the AA metabolic pathway with UHPLC-QQQ-MS/MS embodied the advantages of requiring a low amount of sample, a simple pretreatment process, and the rapid and efficient simultaneous quantification of multiple inflammatory factors. It provided a novel assay method for the pharmacological study of the AA metabolic pathway.